The nonmedical use of prescription ADHD medications: results from a national Internet panel - Williams Rick L; Kroutil Larry A; Novak Scott P; Van Brunt David L (BMC, 2007)
Abstract Background Emerging evidence suggests that nonmedical use (NMU) of prescription attention deficit/hyperactivity disorder (ADHD) medications is rising, but many previous investigations have used clinical or regionally based samples or limited their investigations to stimulants rather than to medications specifically used to treat ADHD. Using an Internet-based epidemiological survey, this paper advances understanding of the prevalence and correlates of NMU of medications used to treat ADHD, sources of diverted medications, motivations for use, and consumption patterns. Methods The study used a self-administered Internet survey of civilian, noninstitutionalized adults (N = 4,297) aged 18 to 49 in the United States. National-level estimates were created using propensity scoring methods and weighting procedures using data from three nationally representative probability surveys: a random-digit dialed telephone survey, the current U.S. Census, and the National Survey on Drug Use and Health (NSDUH). Results Past-year prevalence of NMU of ADHD medications was approximately 2%, with 4.3% reported among those aged 18 to 25 and 1.3% among those aged 26 to 49. Most respondents reporting NMU used on multiple occasions. Receipt of medications for ADHD was a significant correlate of past-year NMU, though most nonmedical users never had a prescription. Among persons who had never been prescribed medication to treat ADHD, friends or family members were the most common source. Productivity was the most frequently endorsed reason for NMU. Alcohol was the substance most commonly used in combination with ADHD drugs. Conclusion Because most prescription ADHD medications currently are highly regulated, policy options for supply-side reduction of nonmedical use may include identifying those medications with lower abuse liability for inclusion on insurance formularies. Patient and physician education programs also may be useful tools to heighten awareness of intentional and unintentional diversion of ADHD medications for nonmedical purposes.